Penentuan Rute Pengambilan Sampah Dengan Menggunakan Metode Clarke & Wright Algorithm Saving Heuristic Di Perusahaan Daerah Kebersihan Untuk Wilayah Bandung Timur - Nugroho, Jatmiko Agung (CV. ITTC INDONESIA, 2024)
Trash problem in Capital City like Bandung City is became concern problem especially by West Java Government that relocating final waste disposal site from Sarimukti located in Padalarang Bandung Barat to final waste disposal site Legoknangka located in East Bandung, but final waste disposal site Legoknangka still in under construction, so the Government of Bandung City made temporary final waste disposal site located in Gedebage on Bandung City, because the distance between final waste disposal site Sarimukti and temporary final waste disposal site are far enough so need to be an assessement for disposal trucking route especially disposal truck various Dump Truck with maximum capacity 12 m³. The purpose for this research is to know, assessment, and analyze result from formation for route with VRP model (Vehicle Routing Problem) which is one of the methods are Saving Heuristic, the main focus on this methods is a big Savings distance, so that the result of distance is the shortest route but still concern maximum truck capacity. The result of this research is change route for truck disposal in East Bandung Area become 3 trucks with total travel distance 98.945 meters or ± 35.000 meters/truck from depot/pool to final waste disposal site, with this occur a savings from total trucks, total travel distance. Where is East Bandung Area usually needs 7 Dump Trucks for service this area, with only 1 truck serve 1-2 temporary dumping ground for travel distance 40.000 meters/truck for serve from temporary dumping ground this time not included travel distance and time travelling for truck to final waste disposal site.